Anteseden and the impact of organizational culture on the civil apparatus of the state - Muhammad Donal Mon; Muhamad Aidil Basri; Golan Hasan; Agustinus Setyawan (Cita Konsultindo Research Center, 2023)
This study investigates the influence of organizational culture on the performance of officials in Batam City. Factors such as competence, innovation, knowledge sharing, and organizational culture are analyzed in relation to staff performance. The study uses a quantitative approach to data collection through questionnaires. Analysis results show a positive relationship between competence, innovation, knowledge sharing, and organizational culture with staff performance. The recommendation of this study is that governments should provide an integrated learning platform and training that fits the positions of staff to improve their performance.